Dynamics of supported ultrathin molybdenum films driven by strong short laser impact. (January 2019) - Khokhlov, V A; Petrov, Yu V; Inogamov, N A; Migdal, K P; Winter, J; Aichele, C; Rapp, S; Huber, H P
Abstract: We consider expansion, break off, and flight of 10 nm molybdenum film deposited onto glass support. These events are initiated by action of subpicosecond laser pulse onto film. Approximations for two-temperature equation of state and electron–ion coupling parameter are developed. Heat conduction is unimportant because film is ultrathin and because radius of a laser beam is rather large ∼ 10 µ m (thus lateral thermal spreading is insignificant at the considered time scale). We use two-temperature one-dimensional hydrodynamic code to follow evolution of laser induced flow. Additional code for treating transmission and reflection of a monochromatic electromagnetic wave is developed. It is applied to describe interference between transmitted and reflected waves in the layered structure appearing thanks to laser induced expansion and separation of a film.